Optimizing Futsal Field Reservation Through FCFS Queueing Algorithm in a Web-Based Booking Platform - Annas, Firdaus (Knowbase : International Journal of Knowledge in Database, 2023)
Advancements in information technology have accelerated the demand for digital systems capable of supporting efficient service management and data processing. Within futsal facility operations, the increasing number of users highlights the need for an automated and reliable field reservation mechanism. Traditional booking practices, which require customers to visit the venue directly to check availability and make reservations, are inefficient, time-consuming, and susceptible to scheduling conflicts. This study proposes a web-based futsal field reservation system that integrates the First-Come, First-Served (FCFS) queueing algorithm to manage booking order. The FCFS algorithm, commonly applied in computing and resource scheduling, processes reservation requests strictly based on arrival time, thereby ensuring fairness and preventing overlapping bookings. The implementation of FCFS within the reservation workflow enables systematic scheduling, minimizes manual errors, and enhances user convenience. Experimental results indicate that the proposed system significantly improves booking efficiency and provides a more transparent, reliable, and organized reservation experience for both customers and futsal operators